Clinical practice guideline for the management of atrial fibrillation for the Peruvian Social Security (EsSalud) - Soto-Becerra, Richard (2019)
Abstract. This article summarizes the clinical practice guide (CPG) for the management of patients with atrial fibrillation (AF) in the Social Security of Peru (EsSalud). Objective. To provide clinical recommendations based on evidence for the management of patients with AF in EsSalud. Methods. A CPG for the management of patients with AF in EsSalud was developed. To this end, a guideline development group (GDG) was established, including medical specialists and methodologists. The GDG formulated 9 clinical questions to be answered by this CPG. Systematic searches of systematic reviews and ,when it was considered pertinent, primary studies were conducted in Medline during 2017. The evidence to answer each of the posed clinical questions was selected. The quality of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the GDG used the GRADE methodology to review the evidence and formulate the recommendations, points of good clinical practice, and the flowchart of the CPG. Finally, the CPG was approved with Resolution No. 91 – IETSI – ESSALUD – 2018. Results. This CPG addressed 9 clinical questions, divided into three topics: prevention of thromboembolic events, maintenance therapy and management of AF. Based on these questions, 12 recommendations (6 strong recommendations and 6 weak recommendations), 29 points of good clinical practice, and 2 algorithms were formulated. Conclusion. This article summarizes the methodology and evidence-based conclusions from the CPG for the management of AF in EsSalud.